Huoxin Pill Attenuates Cardiac Inflammation by Suppression of TLR4/NF-κB in Acute Myocardial Ischemia Injury Rats. (9th July 2020) - Chu, Jianfeng; Zhou, Xueling; Peng, Meizhong; Lu, Yan; Farman, Ali; Peng, Lianli; Gao, Huajian; Li, Qi; Chen, Xintong; Xie, Lingling; Chen, Youqin; Shen, Aling; et al.
Abstract : Huoxin Pill (HXP), a traditional Chinese medicine, has been prescribed widely in the treatment of coronary heart disease, angina pectoris, and other diseases. However, the possible protective mechanisms of HXP on myocardial ischemia remain unclear. In the current study, we investigated the effects and potential mechanism of HXP on myocardial ischemia and cardiac inflammation and the activation of TLR4/NF- κ B pathway. Determination of electrocardiogram, echocardiography, and heart weight index (HWI) indicated that HXP treatment obviously attenuated the elevation of ST-segment, end-diastolic volume, and HWI in the AMI rat model. Enzyme-linked immunosorbent assay (ELISA) demonstrated that Huoxin Pill treatment significantly decreased the levels of CTnT, CK-MB, MDA, IL-6, and TNF- α, while it increased SOD content in serum of the AMI rat model. Moreover, hematoxylin and eosin (HE) and immunohistochemistry (IHC) staining revealed that HXP treatment alleviated pathological change, infiltration of inflammatory cells, levels of IL-6 and TNF- α, and expression of TLR4 and p-NF- κ B in cardiac tissues of the AMI rat model. In conclusion, HXP treatment significantly improves cardiac function and attenuates cardiac inflammation by suppressing the activation of TLR4/NF- κ B pathway in the ISO-induced AMI rat model. This study provides insights into the potential of HXP on prevention and treatment of AMI.